A name for the clade formed by owlet-nightjars, swifts and hummingbirds (Aves) - Sangster, George (Zootaxa, 2005)
Recent phylogenetic studies of non-passerine birds provide congruent support for a clade formed by owlet-nightjars (Aegothelidae) and swifts and hummingbirds (Apodiformes). This clade is here named Daedalornithes (new clade name) based on the principles of phylogenetic taxonomy.